2022
DOI: 10.3389/fmed.2022.925344
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between METS-IR and Serum Ferritin Level in United States Female: A Cross-Sectional Study Based on NHANES

Abstract: AimThe aim of this study was to investigate the association between the metabolic score for insulin resistance (METS-IR) and serum ferritin in females from the United States.MethodsWe conducted a cross-sectional study with 4,182 participants from the National Health and Nutrition Examination Survey (NHANES). We used METS-IR and serum ferritin as the independent and dependent variables in this study and investigated the relationship by using multiple linear regression and verified the non-linear relationship wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Previous studies suggested that age was positively associated with serum ferritin levels [ 41 , 47 ], and that this change was particularly pronounced in people aged 20–50 years [ 48 ], while serum ferritin would remain relatively constant as the body ages [ 49 ]. In previous studies conducted by NHANES, we found a higher proportion of white participants in the group with higher serum ferritin [ 50 , 51 ], which was consistent with our findings. However, in the US population, Black people have a higher prevalence of obesity [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies suggested that age was positively associated with serum ferritin levels [ 41 , 47 ], and that this change was particularly pronounced in people aged 20–50 years [ 48 ], while serum ferritin would remain relatively constant as the body ages [ 49 ]. In previous studies conducted by NHANES, we found a higher proportion of white participants in the group with higher serum ferritin [ 50 , 51 ], which was consistent with our findings. However, in the US population, Black people have a higher prevalence of obesity [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…A former smoker was defined as someone who had smoked more than 100 cigarettes in their lifetime but had currently quit, and a current smoker was defined as someone who smoked more than 100 cigarettes and was presently smoking [ 23 ]. Alcohol consumption was determined by a cut-off of > 12 drinks per year, and no alcohol consumption was defined as consuming less than 12 drinks per year [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…A large cross-sectional study of 21,082 participants by Chen et al 25 found that the increase in METS-IR index was associated with a higher incidence of asthma and an earlier age of first asthma in American adults. Han et al 26 found a positive correlation between METS-IR and serum ferritin in a cross-sectional study of 4182 American women. This correlation was evident among participants ≥ 40 years old.…”
Section: Discussionmentioning
confidence: 97%